2019
DOI: 10.1515/pwp-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Die Chancen und Risiken eines Experience rating in der Arbeitslosenversicherung

Abstract: ZusammenfassungRainer Eppel und Helmut Mahringer beleuchten die Chancen und Risiken unterschiedlicher Gestaltungsvarianten eines Experience rating in der Arbeitslosenversicherung. Hintergrund dafür ist der Befund, dass eine durch pauschale Arbeitgeberbeiträge finanzierte Arbeitslosenversicherung unerwünschte Umverteilungseffekte produziert und Anreize zu vermehrten, häufig nur vorübergehenden Beschäftigungsbeendigungen setzt. Studien zeigen für die Vereinigten Staaten, Kanada und einige Länder Europas, dass di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…On the contrary, many employers interpret long-term unemployment as a negative signal of reduced productivity or willingness to work and are therefore even more reluctant to hire the long-term unemployed than the short-term unemployed (cf. Eppel et al 2018). For this reason, it can be assumed that the long-term unemployed would have been hired less often anyway without the subsidy.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, many employers interpret long-term unemployment as a negative signal of reduced productivity or willingness to work and are therefore even more reluctant to hire the long-term unemployed than the short-term unemployed (cf. Eppel et al 2018). For this reason, it can be assumed that the long-term unemployed would have been hired less often anyway without the subsidy.…”
Section: Resultsmentioning
confidence: 99%
“…Nüß (2018) demonstrated that prolonged periods of unemployment can result in skill decay and labour market discrimination, which in turn reduce an individual's likelihood of being re-employed in the future. This likelihood of being re-employed was estimated by Eppel et al (2018) for Austria. They find a probability of 3.0% for long-term unemployed people finding employment in the following month, compared to 14.2% for the short-term unemployed.…”
Section: Introductionmentioning
confidence: 99%